Analisis Pengaruh Kualitas Pelayanan, Lingkungan Kerja, Beban Kerja Dan Insentif Terhadap Loyalitas Pegawai Pada Rumah Sakit Umum Rantauprapat - Susilawati Susilawati (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the analysis of the influence of service quality, work environment, workload and work environment on employee loyalty at Rantauprapat General Hospital. In testing individually / partially (t test) obtained two variables that have a significant influence and two variables that are not significant to employee loyalty. Where the value of the probability of significant service quality variable (X1) is more than 0.05, which is equal to 0.001 with a value of beta ( ③ ) of 0.500, for the work environment variable (X2) is less than 0.05, which is equal to 0.031 with a value of beta ( ③ ) of 0.361, the workload variable (X3) has a significant probability value of more than 0.05, which is equal to 0.085 with a value of beta ( ③ ) of 0.179, as well as the work environment variable has a significant probability value of more than 0.05 that is equal to 0.056 with a beta value of 0.243. For the results of the analysis based on the F test conducted showed that the quality of service, work environment, workload and work environment simultaneously or together have a significant positive influence on employee loyalty in Rantauprapat General Hospital.